Pengaruh Kompetensi Audit Internal Dan Kualitas Jasa Audit Terhadap Good Corporate Governance (GCG) - Putu Ariasmini Alves; I Gusti Ngurah Sanjaya; I Putu Budi Anggririawan (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2021)
This study aims to analyze the effect of internal audit competence on Good Corporate Governance and the quality of audit services on Good Corporate Governance. The population in this study were all hotels in Badung regency. The data collection method used in this research is by distributing questionnaires online using google form. The sampling technique was carried out by purposive sampling method and based on predetermined criteria, the number of hotels that met the criteria was 62 04 star hotels in Badung regency. Respondents in this study were chief accounting and internal audit within the hotel. The research hypothesis was tested using multiple linear regression with the help of SPSS 22.00 for Windows software. The results showed that the variables of internal audit competence and audit service quality partially had a positive effect on Good Corporate Governance.